2021
DOI: 10.3390/healthcare9020183
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Virtual Reality Exercise Program on Sitting Balance Ability of Spinal Cord Injury Patients

Abstract: (1) Background: Virtual reality (VR) is a useful device for rehabilitation therapy. The purpose of this study was to examine the effect of virtual reality exercise program on sitting balance with spinal cord injury; (2) Methods: 20 subjects who selected on the basis of the screening criteria were divided into the experimental group (n = 10) who underwent the virtual reality exercise program and rehabilitation therapy and the control group (n = 10) who underwent a regular sitting balance training program and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For example, some studies [11], [15] and clinical trials [1], [39] demonstrated that additional core stability exercises performed in clinic or at home with the help of robotic systems or passive devices were useful for improving dynamic sitting balance and trunk control for stroke survivors having an impact also on their daily life activities. Similarly for people with spinal cord injury [25], [26], [28], [40]. Other groups [19], [20], [21] proved the effects of a specific training with extra conditioning exercises for low back muscles strengthening or with a stability ball for reducing back pain of sedentary individuals, or of people with history of chronic low back pain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, some studies [11], [15] and clinical trials [1], [39] demonstrated that additional core stability exercises performed in clinic or at home with the help of robotic systems or passive devices were useful for improving dynamic sitting balance and trunk control for stroke survivors having an impact also on their daily life activities. Similarly for people with spinal cord injury [25], [26], [28], [40]. Other groups [19], [20], [21] proved the effects of a specific training with extra conditioning exercises for low back muscles strengthening or with a stability ball for reducing back pain of sedentary individuals, or of people with history of chronic low back pain.…”
Section: Discussionmentioning
confidence: 92%
“…Future directions and improvements will be to enlarge the testing populations including those with specific needs for sitting balance training e.g., athletes, older adults, or people with chronic low back pain. Moreover, longer training lasting multiple weeks might be another good improvement since it has been already proven that intensive motor training for recovering any upper or lower limb lost or impaired motor abilities has strong effects [11], [26], [38], [41], [42], [44], [45]. Furthermore, to verify if the information on trunk posture we provide during training is fundamental to target and correct wrong behaviors it will be interesting to add a second group that will practice with the same protocol, but without receiving any feedback on trunk posture during the training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each session lasts thirty minutes twice a week for eight weeks. Equilibrium functions were measured according to the protocols described in the literature [66].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that group A improved further, in terms of balance and functioning. Furthermore, Lee and Lee [8] investigated the effect of a VR program on the balance in a sitting position in patients with SCI. The study involved 20 patients, who were equally divided into two groups.…”
Section: Literature Reviewmentioning
confidence: 99%